Endovascular Repair of Ruptured Popliteal Artery Aneurysms: A Case Report and Review of the Literature. (2016) - Brown, S.L.; Lewis, M.; Morrow, D.R.
Abstract : Objective/Background: The objectives were to report the management and outcomes of a 96-year-old man who presented with an acutely swollen right leg due to a ruptured popliteal aneurysm, and to review the relevant literature. Methods: A ruptured popliteal artery aneurysm is a rare diagnosis and is one that is often missed at time of presentation. Previous case reports have documented successful outcomes following surgical repair, and a smaller number following endovascular repair. This is a case report of a 96-year-old man who eventually underwent endovascular repair of a ruptured popliteal artery aneurysm after a delay in diagnosis. A literature review was performed to analyse published data in this field. Results: The patient underwent an uncomplicated endovascular repair with a GORE ® VIABAHN ® stent. A 15-week follow-up ultrasound demonstrated biphasic flow in a patent stent-graft with an unchanged aneurysm sac size and no evidence of an endoleak. A review of the literature demonstrated nine cases of ruptured non-mycotic popliteal artery aneurysms treated endovascularly. Seven cases survived the postoperative period, three had no follow-up recorded, and four cases had patent stent-grafts at time of follow-up. Conclusion: Safe and effective endovascular repair of a ruptured popliteal artery aneurysm with endograft patency seen at the 15-week follow-up is reported. Review of the literature suggests that open repair remains the first-line management choice; however, endovascular repair is a valuable alternative. There is a further need for longer-term monitoring of endograft patency following endovascular repair. Highlights: Ruptured popliteal aneurysm is rare. Diagnosis is easily missed unless specifically considered. Endovascular repair appears to be safe and effective.